Whiteness feels good here: interrogating white nationalist rhetoric on Stormfront - Hartzell, Stephanie L. (Communication and critical/cultural studies, 2020)
This essay adopts a critical rhetorical perspective attuned to affect to investigate white nationalist rhetoric on Stormfront, a popular white nationalist message board. My analysis illuminates how Stormfront attempts to appeal to mainstream white audiences by resisting normative expectations and affects articulated with white supremacy and (re)constructing white nationalism as a formation of white racial consciousness articulated with communal belonging, common sense, and pride. On Stormfront, affect is mobilized discursively to challenge colorblindness, construct rhetorical distance between white nationalism and white supremacy, and strategically negotiate white (dis)comfort with direct discourse on race to compel affective investments in white nationalism.